Management of women with hypertensive disorders in pregnancy in the immediate postpartum period: a retrospective review of practices in a busy tertiary hospital in Gauteng, South Africa - Mashoene, Rangwato Pearl (My University, 2024)
Background Hypertensive disorders in pregnancy (HDP) are a leading cause of maternal morbidity and mortality globally, accounting for14,8% of the total maternal deaths in South Africa. The burden of HDP continues beyond pregnancy with a third of women continuing to have persistent hypertension beyond pregnancy. Objective To describe the management and outcomes of women with hypertension in pregnancy during the immediate postpartum period. Methods This was a prospective study conducted at the postnatal ward of Chris Hani Baragwanath Hospital over 12 months on women with hypertensive disorders of pregnancy, who still required blood pressure treatment postdelivery. Post ethics approval, data were collected from patients and their files managed using REDCap® electronic data capture tools hosted by the University of the Witwatersrand. Results A total of 200 participants were included,163 (81,5%) had an abnormal blood pressure of more than the target BP of ³150/100mmHg within 24 hours of delivery and 37 (18,5%) within 48 hours at an average 3 day duration of stay for BP control. The choices of drugs for blood pressure control were not in line with the stepwise national guidelines on postpartum hypertension management, the commonest of which were Nifedipine, Enalapril, and Methyldopa. Sixty-seven participants (33,5%) still had uncontrolled blood pressure, higher than target BP at the time of discharge but less than severe hypertension of 160/110 mmHg. All discharged participants including those on 3 agents for BP were given a routine postnatal follow up at a local clinic. Conclusion The high number of patients that required treatment within 24 hours of delivery has highlighted the need for continued vigilance and enhanced postnatal care by clinicians beyond delivery. This includes strict adherence to institutional and national guidelines and protocols on the management of hypertension postdelivery and proper follow-up channels at discharge.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Obstetrics and Gynaecology to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Hypertensive disorders; Pregnancy; Women